2015
DOI: 10.1155/2015/793292
|View full text |Cite
|
Sign up to set email alerts
|

Impairments of Antigen-Presenting Cells in Pulmonary Tuberculosis

Abstract: The phenotype and functional properties of antigen-presenting cells (APC), that is, circulating monocytes and generated in vitro macrophages and dendritic cells, were investigated in the patients with pulmonary tuberculosis (TB) differing in lymphocyte reactivity to M. tuberculosis antigens (PPD-reactive versus PPD-anergic patients). We revealed the distinct impairments in patient APC functions. For example, the monocyte dysfunctions were displayed by low CD86 and HLA-DR expression, 2-fold increase in CD14+CD1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 27 publications
(27 reference statements)
3
9
1
2
Order By: Relevance
“…Such suppressive monocytes could also induce regulatory CD8 + T lymphocytes that could convert the potentially protective cytotoxic CD8 + T cells to suppressive CD8 + T lymphocytes . Finally, suppressive CD14 + monocytes are also characterized by a down regulation of the expression of HLA‐DR, CD80 and CD86 molecules, a phenotype previously reported for the monocytes from patients with aTB, and confirmed in our study for the CD86 expression.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Such suppressive monocytes could also induce regulatory CD8 + T lymphocytes that could convert the potentially protective cytotoxic CD8 + T cells to suppressive CD8 + T lymphocytes . Finally, suppressive CD14 + monocytes are also characterized by a down regulation of the expression of HLA‐DR, CD80 and CD86 molecules, a phenotype previously reported for the monocytes from patients with aTB, and confirmed in our study for the CD86 expression.…”
Section: Discussionsupporting
confidence: 89%
“…2 As the characterization of monocyte and DC subpopulations is only possible using very sensitive flow cytometer, only few data concerning the influence of Mtb infection on these subpopulations has been reported so far. [3][4][5][6][7] Here we compare the proportions of circulating monocytes and DC subpopulations in patients with aTB, subjects with LTBI and noninfected controls and we further analyzed the expression of stimulatory, inhibitory, or apoptosis-inducing molecules expressed by these cell subpopulations. CD86 expression was chosen to analyze the expression of costimulatory molecules associated with APC activation.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, this was the first study on IL-6 mRNA expression in TBDM, TBDM HHC in response to M.tb Ag85A. IL-6 mRNA expression was significantly high in PTB patients when compared to HC which was in contrast to a Korean study [35] where it was similar in PTB patients and in HCs. Distinct results were reported in a study which has shown low IL-6 expression in the ESAT-6 stimulated PBMCs of PTB patients when compared to the LTBI individuals without any difference in the HCs [33].…”
Section: Discussioncontrasting
confidence: 84%
“…Its secretion was low in PTB when compared to HC in contrast to an Indonesian study where it was comparatively high [29]. A study by Jo et al [34] and Ludmila et al [5] reported that there was no statistical difference in the IL-6 production on stimulation with Ag85B and PPD in PTB patients and HCs and PTB HHC have not shown any variation from the HCs [35,36]. Our results were similar to a study where significantly higher levels were induced in PTB HHC when compared to PTB patients on proteomic analysis identification of immune-reactive T cell antigens [37].…”
Section: Discussionmentioning
confidence: 76%
“…The poor performance of BCG in TB-endemic areas can be rationalized with multiple explanations. BCG protects the childhood but not adult manifestation of TB [27][28][29][30]. Signifying that it lacks the antigenic repertoire that is required in inducing long-lasting protective memory T cells.…”
Section: Discussionmentioning
confidence: 99%